The symbiotic relationship between puppetry and disability: The emergence of a strong contemporary visual language. (1st July 2020) - Fisher, Emma
This article will discuss how the puppet's body is the perfect vessel to reclaim the voices of those that have been 'othered'. It examines the history of the fractured puppet and the emergence of disability-affirmative puppet theatre in the twenty-first century, exploring the puppet's ability to fracture, reform and move in new and exciting ways that allow different approaches of expression; these seek to challenge how the body, the puppeteer and the puppet are viewed. I will examine how puppet plays, A Square World, Meet Fred, The Iron Man and my own show Pupa, represent disability through puppets' bodies in new and interesting ways. Through the use of the puppet's body, these shows seek to shine a light on the absurdity of an exclusive world and make us question the cultural constructions around the disabled and puppet body.